(untitled) (Global Journal of Human-Social Science, 2013)
By extending the deterrence theory to national level, the current study tested the hypothesis that ineffective government is largely responsible for higher homicide rate in a nation. The homicide data required for the test were collected from the World Health Organization and the information on governance from the World Bank’s World Governance Indicators for 122 nations. The results from the regression models supported the deterrence theory. An ineffective and dysfunctional government was one of the primary sources for a nation’s high homicide rate. Also, other control variables, such as relative poverty and ethnic heterogeneity, were positively related to the homicide rate in a nation.